The determinants of the propensity to receive publicly funded home care services for the elderly in Canada: A panel two-stage residual inclusion approach - Gustavo Mery; Walter P. Wodchis; Audrey Laporte (Health Economics Review, 2016)
The role of Home Care (HC) services for the elderly will be increasingly important in meeting populations' future needs for care. HC services include Home Health Care (HHC) and Homemaking/Personal Support (HMPS), distinction rarely seen in the literature. This paper argues that it is important to distinguish between these types of HC, since the factors that drive the likelihood of the receipt of each type of care may differ, and also to investigate the interrelationship between them. We explored the interrelationship between receipt of publicly funded HMPS and HHC, and the determinants of the receipt of each type of services. A Panel Two-Stage Residual Inclusion approach was applied to estimate the likelihood of the receipt of HC services using data for those aged 65 and over from 9 biannual waves of the Canadian National Population Health Survey (1994-95 to 2010-11). We found that there are in fact differences in the determinants of the likelihood of HHC and HMPS receipt. Moreover, receipt of publicly funded HMPS was found to be complementary with receipt of publicly funded HHC services after adjusting for functional and health status. Dependence on help with activities of daily living, health status, household arrangement, and income were found to be determinants of the propensity to receive both publicly funded HHC and HMPS services. This study aims to contribute to the existent literature by taking a step toward explicitly modelling the potential interaction between the determinants of the receipt of different types of HC services simultaneously, as a system. Our methodological approach, a Panel Two-Stage Residual Inclusion method, seems to effectively address problems that are known to be a source of bias in the literature.
Keywords: 330; Home care; Elderly; Long-term care; Public provision; Complementary effect; Determinants